PERBANDINGAN INTERVAL PEMBERIAN MISOPROSTOL 25 μg PERORAL 4 JAM DAN 6 JAM DALAM INDUKSI PERSALINAN - , Agus Wahyu Widayat ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background:. Labor induction is the most commonly performed obstetric intervention. Misoprostol is a synthetic prostaglandin E1 analogue used in labor induction. With oral use, plasma concentration increases rapidly and reaches peak concentration between 7.5 to 30 minutes (average 14 minutes) after administration, then decreases gradually over 120 minutes and plateaus at that concentration. Induction by oral misoprostol is effective in inducing vaginal birth. Although it is not able to induce labor as fast as pervaginal induction, incidence of hyperstimulation and fetal distress is lower in peroral induction at the same dosage and when administered orally, it is advisable that no more than 50g be used. Objective:. To know the effectiveness and safety of administering misoprostol 25µg peroral in the induction of labor between drug administration intervals of 4 and 6 hours Design of study: Prospective, Randomized Controlled Trial Material and method: Three hospitals (Dr. Sardjito hospital yogyakarta, Banjarnegara hospital and Muntilan hospital) and 2 primary health care centres (PHC Tegalrejo and PHS Mergangsan) were used in this study. Research subjects were pregnant women with indications for labor induction, who meet the inclusion criteria and do not meet any exclusion criteria. The group which received misoprostol 25µg peroral every 4 hours was the intervention group and subjects who received misoprostol 25µg peroral every 6 hours were the control group. Research was conducted from 10 August 2010 till 10 januari 2011. The observed results were the time interval between the administration of the drug and the onset of stage 2 for each group and side effects to the mother and baby. The data is analysed using a statistic package program using the computer. Chi square test, t-test and regression analysis was used to perform statistical test. Results: As many as 120 subjects were divided into 2 intervention groups . For the 4 hour interval group, the average time interval between induction of labor and stage 2 labor is 11.87+4.27 minutes, whereas in the 6 hr interval group, the average time interval between induction of labor and stage 2 labor is is 17.77+11.66 minutes. There is a significant difference (p=0.01) between the two groups. No signs of hyperstimulation, tachysystole and shivering were found in both groups. There was no significant difference in the incidence of side-effect of nausea between the two groups (1.7% vs 6.7%